A Systematic Review of Green Human Resource Management: Innovations and Their Impact on Employee Behavior - Afifa Dian Islami; Aulia Nur Azizah; Demelka Delima; Jauharoh Wilda Arihabsari; Nazwa N urahmah; Riva Khoerunnisa; Tabitha Nathali Nugroho; Xue Chenjie (International Journal of Management and Economic Research (IJOMER), 2025)
This study systematically reviews the recent literature on Green Human Resource Management (GHRM) and its influence on employee green behavior (EGB) across various industries from 2015 to 2025. GHRM, which integrates environmental values into HR practices such as recruitment, training, and rewards, is increasingly recognized as a strategic approach to promoting sustainability and pro-environmental actions in organizations. Using a comprehensive search strategy across multiple academic databases and guided by the PCO (Population, Comparison, Outcome) framework, 38 empirical studies were selected and analyzed. Thematic synthesis revealed that the majority of research (81.58%) focuses on employee behavior, while environmental performance, job satisfaction, and organizational performance remain less explored. Key mediators and moderators identified include green organizational commitment, psychological climate, knowledge sharing, and green transformational leadership. The findings highlight that innovative GHRM practices not only foster employee engagement in sustainability initiatives but also contribute to organizational reputation and compliance with evolving environmental standards. However, challenges such as limited resources and resistance to change persist. This review underscores the need for further research on underexplored outcomes and provides practical insights for aligning HR strategies with environmental sustainability goals.